Production, purification and crystallization of a trans‐sialidase from Trypanosoma vivax. Issue 5 (1st May 2015) - Haynes, Carole L. F.; Ameloot, Paul; Remaut, Han; Callewaert, Nico; Sterckx, Yann G.‐J.; Magez, Stefan
<x xml:space="preserve">Abstract</x> Sialidases and trans‐sialidases play important roles in the life cycles of various microorganisms. These enzymes can serve nutritional purposes, act as virulence factors or mediate cellular interactions (cell evasion and invasion). In the case of the protozoan parasite Trypanosoma vivax, trans‐sialidase activity has been suggested to be involved in infection‐associated anaemia, which is the major pathology in the disease nagana. The physiological role of trypanosomal trans‐sialidases in host–parasite interaction as well as their structures remain obscure. Here, the production, purification and crystallization of a recombinant version of T. vivaxtrans‐sialidase 1 (rTvTS1) are described. The obtained rTvTS1 crystals diffracted to a resolution of 2.5 Å and belonged to the orthorhombic space group P212121, with unit‐cell parameters a = 57.3, b = 78.4, c = 209.0 Å.